(untitled) (Global Journal of Medical Research, 2020)
Background: Aging is often associated with the incidence of degenerative diseases such as cardiovascular, cerebrovascular diseases, diabetes, osteoporosis, and cancer, which affects dietary eating patterns in older adults. With advancing age, there is a decline in appetite and a reduced affinity to food. However, the eighty million citizens of West Bengal including the older adults have a craving for sweets. Therefore, the present study aims to evaluate the sensory and chemical evaluation of Sandesh prepared from soymilk and dates adhering to nutritional needs and dietary preference towards sweets for older adults. Method: Sandesh is prepared with the substitution of traditional milk chenna (fresh, unripened curd cheese made from cow milk/ buffalo milk) with soy milk and dates syrup.